During apoptosis HMGB1 is translocated into apoptotic cell-derived membraneous vesicles - Schiller, Martin; Heyder, Petra; Ziegler, Saskia; Nießen, Anna; Claßen, Laura; Lauffer, Anna Marie; Lorenz, Hanns-Martin (Autoimmunity, 2013)
High mobility group box protein B1 (HMGB1), a nuclear protein reportedly involved in the structural organisation of DNA, is released from necrotic cells or upon cellular activation. After its release into the extracellular space, HMGB1 serves as a mediator of inflammation. In contrast to necrotic cells, apoptotic ones usually do not release HMGB1. Formation and release of membraneous vesicles is a well-known feature of apoptotic cell death. Only recently, subcellular membrane vesicles, such as those released during apoptotic cell death have been identified as immune regulators and as mediators of cell to cell communication. We and others have previously detected nuclear antigens within apoptosis-released membranous vesicles and HMGB1 together with nuclear antigens has been discussed to be a key player in etiology and pathogenesis of autoimmune diseases. On this background, we analysed whether HMGB1 is included in the membraneous vesicles generated by apoptosing cells. Employing immune blots we observed abundand amounts of HMGB1 in the fraction of the small membraneous particles isolated from cell culture supernatants and conclude that HMGB1 is translocated into vesicles generated during apoptosis.